APPLICATION OF PROBLEM BASED INSTRUCTION (PBI) LEARNING MODEL WITH THE THEME WATER POLLUTION FOR SEVENTH CLASS STUDENT - ANANDARU, DENNY (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
The objective of this research is: 1) Describe the feasibility learning in the application of PBI learning model with the theme water pollution for seventh class students of 9 Junior high school Surabaya. 2) Describe student learning outcomes in the affective and cognitive domain to application of PBI learning model with the theme water pollution, 3) Describe students responses to application of PBI learning model with the theme water pollution. This research is quasi-research type with one shot case study method. The research applicated in 9 junior high school Surabaya, research objective is VII-G class with 38 students. The data was analyzed descriptively, and show that: 1) the feasibility learning in the application of PBI learning model with the theme water pollution for seventh class students of 9 Junior high school Surabaya performing well, 2) the completeness of student learning outcomes based on minimal criteria for completeness with pencentage of 90% and the completeness of objective learning with percentage of 95%. The student learning outcomes in affective domain categorized as good and very good, 3) 85% of students gives positive responses to application of PBI learning model. Key Word: Problem Based Instruction (PBI), Kognitive, Affective, Water pollution.